Suppression of Age-Related Salivary Gland Autoimmunity by Glycosylation-Dependent galectin-1-driven Immune Inhibitory Circuits - Martínez Allo, Verónica Candela (2020)
Aging elicits quantitative and qualitative changes in different immune components, leading to disruption of tolerogenic circuits and development of autoimmune disorders. Galectin-1 (Gal1), an endogenous glycan-binding protein, has emerged as a regulator of immune cell homeostasis by shaping the fate of myeloid and lymphoid cells. Here, we demonstrate that aged Gal1-null mutant (Lgals1−/−) mice develop a spontaneous inflammatory process in salivary glands that resembles Sjögren's syndrome. This spontaneous autoimmune phenotype was recapitulated in mice lacking β1,6N-acetylglucosaminyltransferase V (Mgat5), an enzyme responsible for generating β1,6-branched complex N-glycans, which serve as a major ligand for this lectin. Lack of Gal1 resulted in CD11c+ dendritic cells (DCs) with higher immunogenic potential, lower frequency of Foxp3+ regulatory T cells (Tregs), and increased number of CD8+ T cells with greater effector capacity. Supporting its tolerogenic activity, Gal1 expression decreased with age in autoimmunity-prone nonobese diabetic (NOD) mice. Treatment with recombinant Gal1 restored tolerogenic mechanisms and reduced salivary gland inflammation. Accordingly, labial biopsies from primary Sjögren's syndrome patients showed reduced Gal1 expression concomitant with higher number of infiltrating CD8+ T cells. Thus, endogenous Gal1 serves as a homeostatic rheostat that safeguards immune tolerance and prevents age-dependent development of spontaneous autoimmunity.